Diverted negative triangularity plasmas on DIII-D: the benefit of high confinement without the liability of an edge pedestal. (23rd September 2021) - Marinoni, A.; Austin, M.E.; Hyatt, A.W.; Saarelma, S.; Scotti, F.; Yan, Z.; Chrystal, C.; Coda, S.; Glass, F.; Hanson, J.M.; McLean, A.G.; Pace, D.C.; et al.
Abstract: Diverted discharges at negative triangularity on the DIII-D tokamak sustain normalized confinement and pressure levels typical of standard H-mode scenarios ( H 98 y 2 ≃ 1, β N ≃ 3) without developing an edge pressure pedestal, despite the auxiliary power far exceeding the L → H power threshold expected from conventional scaling laws. The power degradation of confinement is substantially weaker than the ITER-89P scaling, resulting in a confinement factor that improves with increasing auxiliary power. The absence of the edge pedestal is beneficial in several ways, such as eliminating the need for active mitigation or suppression of edge localized modes, low impurity retention and a reconstructed scrape-off layer heat flux width at the mid-plane that exceeds the ITPA multi-machine scaling law by up to 50%. Together with technological advantages granted by placing the divertor at larger radii, plasmas at negative triangularity without an edge pedestal feature both core confinement and power handling characteristics that are potentially suitable for operation in future fusion reactors.